Systematic Literature Review : Analisis Bahan Ajar Interaktif Berbasis Etnomatematika Dalam Pembelajaran Matematika di Era Digitalisasi - Isnaini, Isnaini (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to conduct a systematic literature review on the analysis of ethnomathematics-based interactive teaching materials in mathematics learning in the digital era. This study uses the Systematic Literature Review (SLR) method. Articles were searched through the Google Scholar, Sinta, and Directory of Open Access Journals (DOAJ) databases from the last 5 years of publications from 2019 to 2024. Based on standardized acceptance criteria, 20 articles were obtained which were used as initial research. Each component was recorded and then classified based on title, year of study, level of education, and type of teaching materials used. Based on the results of the literature review by the researcher, several findings and conclusions were obtained, including: 1) the use of E-modules is very well known and widely used by researchers in implementing a learning concept and E-modules are also a reference for teaching materials that are widely studied by researchers in various studies. 2) the average percentage level of all articles studied shows an effectiveness of 85% so that all teaching materials studied are included in the very good category or can be said to be effective.